Navigating Terrorist Innovation: A Proposal for a Conceptual Framework on How Terrorists Innovate - Lubrano, Mauro (Terrorism and political violence, 2023)
While many scholars acknowledge terrorist innovation as a crucial issue, it still remains a rather under-researched phenomenon. This paper intends to map the field in order to propose an original conceptualization of terrorist innovation. In doing so, it draws on the Terrorism Studies, Strategic Studies, and Business Studies literatures to propose a definition of terrorist innovation, while also distinguishing between the categories of tactical, operational, and strategic innovation. Additionally, enriched with empirical observations, the paper explores potential drivers of the innovation process. Finally, it provides a set of suggestions for future research.